Reading with new tools: an evaluation of Personal Digital Assistants as tools for reading course materials - Jenny Waycott (Association for Learning Technology, 2002)
Lightweight, palmtop devices such as personal digital assistants (PDAs) can now be used for reading electronic text, opening up their potential as learning tools. This paper reports a study that evaluated the use of PDAs for reading course materials by students on an Open University master's course. The research is grounded in activity theory, which provides a useful framework for examining how the introduction of a new tool changes an existing activity. Student perceptions of the possibilities and constraints of the PDA, as determined by questionnaires and interviews, reveal the impact the new tool had upon reading. The PDA constrained reading with limitations such as the small screen size, new requirements for navigating through the text and awkward methods for taking notes. These conditions made it difficult for students to skim-read the text, to move back and forth within the document and to interact with the text as easily as they could with paper. Nevertheless, students welcomed the opportunity to have the course materials on a portable, lightweight device that could be used at any time and in any place. This made it easier to fit the reading activity around the various other activities in which students were involved In addition, the PDA was used in conjunction with existing tools, such as the printed version of the course materials and the desktop computer. Therefore, it was not seen to replace paper but rather to extend and complement it. The findings are discussed using concepts from activity theory to interpret how the new tool modified the reading activity.